2004
DOI: 10.1104/pp.103.033431
|View full text |Cite
|
Sign up to set email alerts
|

When Defense Pathways Collide. The Response of Arabidopsis to a Combination of Drought and Heat Stress  

Abstract: Within their natural habitat, plants are subjected to a combination of abiotic conditions that include stresses such as drought and heat. Drought and heat stress have been extensively studied; however, little is known about how their combination impacts plants. The response of Arabidopsis plants to a combination of drought and heat stress was found to be distinct from that of plants subjected to drought or heat stress. Transcriptome analysis of Arabidopsis plants subjected to a combination of drought and heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

92
1,386
14
15

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 1,472 publications
(1,507 citation statements)
references
References 44 publications
92
1,386
14
15
Order By: Relevance
“…This observation is consistent with results obtained in a study which showed polyols can be synthesised from their analogue sugars under reducing conditions (Pavli et al, 2013). The accumulation pattern observed in this study agrees with the findings by other researchers that polyols function in osmoregulation under drought stress (Rizhsky et al, 2004). Mannitol confers stress tolerance through actively scavenging hydroxyl radicals and is found in lower concentrations in DT cultivars than in DS wheat crops (Abebe et al, 2003).…”
Section: Carbohydrates Metabolismsupporting
confidence: 92%
“…This observation is consistent with results obtained in a study which showed polyols can be synthesised from their analogue sugars under reducing conditions (Pavli et al, 2013). The accumulation pattern observed in this study agrees with the findings by other researchers that polyols function in osmoregulation under drought stress (Rizhsky et al, 2004). Mannitol confers stress tolerance through actively scavenging hydroxyl radicals and is found in lower concentrations in DT cultivars than in DS wheat crops (Abebe et al, 2003).…”
Section: Carbohydrates Metabolismsupporting
confidence: 92%
“…Heat-induced expression of sHSP is one of the most sensitive, rapid and short lasting molecular responses in plants (Merquiol et al, 2002;Sun et al, 2002;Rizhsky et al, 2004). To determine when the heat-response becomes saturated and how accurate is the control of expression by the duration of the heat-treatment, we measured the GUS activity resulting from increasing periods of heat-exposure at 38°C.…”
Section: Optimal Heat Inducing Treatments Cause No Apparent Damagesmentioning
confidence: 99%
“…Moreover, it also alters the physiological processes such as photosynthesis, accumulation of lipids and transcript expression [52,53].…”
Section: Combined Effects Of Drought and Heat Stressmentioning
confidence: 99%